The marriage lie - Belle, Kimberly (Mira Books, 2016)
"Iris and Will have been married for seven years, and life is as close to perfect as it can be. But on the morning Will flies out for a business trip to Florida, Iris's happy world comes to an abrupt halt: another plane headed for Seattle has crashed into a field, killing everyone on board and, according to the airline, Will was one of the passengers. Grief stricken and confused, Iris is convinced it all must be a huge misunderstanding. Why did Will lie about where he was going? And what else has he lied about? As Iris sets off on a desperate quest to uncover what her husband was keeping from her, the answers she finds shock her to her very core." -- From publisher's description.